Exchange rate determination puzzle : long run behavior and short run dynamics - Butgereit, Falkmar (Hamburg: Diplomica, 2010)
The book examines exchange rate driving forces over longer periods and the low predictive power of standard macroeconomic exchange rate models. It also assess the successes in forecasting and explaining exchange rates.
Includes bibliographical references (pp. 109-113).
usc 05/12/17
Loans
Keywords: Foreign exchange rates